2007
DOI: 10.1021/jp072566g
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Molecular Properties and Decomposition Products of 1-AzidoalkynesA Challenge for Experimentalists

Abstract: In this publication, a characterization of different azidoalkyne compounds using high-level ab initio quantum chemical methods is presented. For this purpose, the molecular structures and the 13C NMR chemical shifts have been calculated at the MP2 and CCSD(T) level of theory and the influence of zero-point vibration as well as the solvent on the chemical shifts are discussed. Furthermore, a comparison of the energy barriers of the decomposition under N2 separation for a set of 1-azidoalkynes with different fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 59 publications
(101 reference statements)
2
34
0
Order By: Relevance
“…The decomposition of ethynyl azide 6 is expected to lead to cyano(trimethylsilyl)carbene (8). The formation of this short-lived species is also supported by quantum chemical calculations that explained the generation of 8 from 6 through a synchronous reaction without a nitrene intermediate [17,21] (Figure 3). The activation barrier for this process was calculated to amount 20-22 kcal·mol −1 , and such a low value corresponds to the fact that 6 is a highly unstable compound.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The decomposition of ethynyl azide 6 is expected to lead to cyano(trimethylsilyl)carbene (8). The formation of this short-lived species is also supported by quantum chemical calculations that explained the generation of 8 from 6 through a synchronous reaction without a nitrene intermediate [17,21] (Figure 3). The activation barrier for this process was calculated to amount 20-22 kcal·mol −1 , and such a low value corresponds to the fact that 6 is a highly unstable compound.…”
Section: Resultssupporting
confidence: 54%
“…The latter method was also utilized to analyze unstable 3 in the gas phase or in argon matrix, and to monitor the thermal or photochemical decay to generate cyanocarbene 4 [15,16]. In the case of the parent compound 3, previous ab initio studies predicted the highest barrier for the loss of dinitrogen, whereas ethynyl azides with a substituent at C-2 should more easily undergo the cleavage reaction [17]. Especially, 1-azidoethynes with a donor substituent Unfortunately, the parent compound 3 is a very explosive substance, and even recondensation of its solution under reduced pressure can lead to an explosion.…”
Section: Introductionmentioning
confidence: 99%
“…196 However, the known 197 trapping products of 306 including the cyclopropane framework cannot be detected when 304 was treated in the presence of cyclohexene or tolane. 39 Attempts to generate and to trap 1 -azido -2 -phenylethyne 157,193,196,198,199,201,202 process. 196a But alternative routes leading from 304 to 308 without the intermediary 1 -azidoalkyne 305 were also discussed.…”
Section: Generation Of Ethynyl Azidesmentioning
confidence: 99%
“…196a But alternative routes leading from 304 to 308 without the intermediary 1 -azidoalkyne 305 were also discussed. 201 When the experiment starting with 310 was repeated quite recently, it has been shown that the real product 315 (10% yield), resulting via 306 , was erroneously taken for 312 . 196b Quite recently, it has been shown that irradiation of 304 in dichloromethane at − 70 ° C induced the complete transformation to the highly unstable heterocycle 307 generated in 90% yield and characterized by its NMR data.…”
Section: Generation Of Ethynyl Azidesmentioning
confidence: 99%
See 1 more Smart Citation